Sairī dar mud wa libās-i daura-i qāǧār - Mubīnī, Mahtāb ca. 1978/79-; Asadī, Aʿẓam ca. 1980/81- (Murakkab-i Sapīd, 2017)
Iran -- Kleidung -- Mode -- Tracht -- Kadscharenzeit 1794-1925 ; Clothing and dress -- Iran -- History -- 1779-1925 ; Fashion -- Iran -- History -- 19th century